HUBUNGAN JENJANG KARIR DENGAN KEPUASAN KERJA PERAWAT - Eva Kartika Hasibuan; Masri Saragih; Erwin Silitonga (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Job satisfaction is an employee's attitude towards work related to work situations, cooperation between employees, rewards received at work, and matters relating to physical and psychological factors. In Indonesia, there are 55.8% of nurses in government hospitals experiencing low job satisfaction. There are several factors that influence job satisfaction including salary earned, organizational culture, relationships with coworkers, supervision, and career development. Career level is one of the efforts to realize nurse job satisfaction. Nursing career level is the implementation of several career plans that have been determined to provide nurses with positions/levels that are in accordance with the education, abilities, skills and competencies of nurses. The purpose of this study was to find out the career level relationship with Job Satisfaction of nurses at Sari Mutiara General Hospital Lubuk Pakam. The research design used is descriptive correlation with cross sectional design. The population in this study were all nurses at Sari Mutiara General Hospital Lubuk Pakam. The sample in this study amounted to 56 people obtained by using total sampling. The data collection tool uses a questionnaire sheet. The statistical test used was the chi square test. The results showed the majority of respondents had a high career level 69,6% and respondents’ performance satisfaction was satisfied as much as 67,8%. Based on the results of the Chi-Square statistical test value = 0,017 (p <0,05) which means that there is arelationship of career level with the satisfaction of nurse performance at Sari Mutiara General Hospital Lubuk Pakam It is recommended for nurses to improve their skills through training and education facilitated by hospitals.